PENENTUAN KOEFISIEN TEKANAN TANAH KESAMPING "AT REST" (Ko) DARI TANAH GAMBUT BERSERAT - Wismantara, I Gusti Nyoman; Budiarnaya, Putu (Jurnal Ilmiah Telsinas, 2018)
One of the most important soil parameters to design bearing capacity of a deep foundaton is at rest lateral pressure coefficient (Ko). Ko is the coefficient of lateral earth pressure under condition of no lateral deformation. For sand and clay soils, the Ko value can be obtained using mathematics formula; it is a function of an effective internal friction angle (f') or plastic index (PI) of the soil. For peat soil, however the Ko value can not be determined using the mathematics formula developed for sand and clay soils mention above. It has to be measured directly from laboratory test using a Ko-test tube. Unfortunately, that apparatus is not available in the market.Due to that reason, the first step of the research carried out. herein is to build the Ko-test tube apparatus; afterward, it is used to determine the Ko value of peat taken from Pekantua, Riau.The Ko-test tube was built as suggested by Abdelhamid and Krizek; it was calibrated with water to determine the relationship between horizontal strain of the Ko-test tube wall and radial stress. By using the apparatus, the Ko of sand was determined ; the result obtained is then compared to the Ko obtained from Jaky's formula. Whenever that apparatus gave a satisfactory result of Ko, the testing was 50 KPa, 100 KPa, 200 KPa and 400 KPa for loading and unloading conditions.The results show that the calibration result of the Ko-test tube can be expressed as linear aquation, that is, sr = 2.98 x 106e average (sr in KPa). The Ko of sand determined using the Ko-test built is comparable to that obtained using jaky's formula, that is 0.46. Under unloading condition, the Ko value of peat is constant 0.32; under unloading condition the Ko is not constant but it is function of OCR in which the increase of OCR is companied with the increase of Ko; the Ko is various between 0.32-0.44.